When Science Becomes Engineering - Mitcham, Carl (NOvation — Critical Studies of Innovation, 2024)
The core insight of this thoughtful and provocative article is that science has become engineering and must be re-governed appropriately. Science today is as much artefact constructing as it is knowledge-producing. Certified knowledge is found through certified construction; science has become technoscience. As such, received practices of and models for governance need re-examining. It is not possible here to address the full range of insights and questions that René von Schomberg’s challenging paper puts on the table. His argument is clearly the outgrowth of years of critical reflection in the science policy trenches of the European Commission. I would wager that there’s no one who has thought longer, harder, and at greater depth about these issues. I will concentrate my comments on the question concerning engineering.